2013 IEEE Grenoble Conference 2013
DOI: 10.1109/ptc.2013.6652303
|View full text |Cite
|
Sign up to set email alerts
|

On the analysis of the dc dynamics of multi-terminal VSC-HVDC systems using small signal modeling

Abstract: In this paper, an analysis of the dc dynamics of multiterminal VSC-HVDC systems using the small signal modeling method is presented. Usually, the VSC controllers are designed under the consideration that they operate independently of each other. However, the possible interactions among them and the dc grid should be studied, especially in multi-terminal topologies. In this paper, three VSC-HVDC systems are modeled and, after linearization, the eigenvalues of the system are calculated for different loading cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…The basis of the procedure was to implement state space models of the individual elements to be later interconnected as shown in Figure 1, where two converters are connected to the HVDC grid (a cable). In [10] the eigenvalues of the system were calculated for a two-terminal and a threeterminal HVDC systems and it was found that undamped oscillations appeared when the power injected by VSC 1 (which controls the direct voltage) exceeds a certain value below the rated power, which, in the studied case was 0.8 pu.…”
Section: Eigenvalues Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The basis of the procedure was to implement state space models of the individual elements to be later interconnected as shown in Figure 1, where two converters are connected to the HVDC grid (a cable). In [10] the eigenvalues of the system were calculated for a two-terminal and a threeterminal HVDC systems and it was found that undamped oscillations appeared when the power injected by VSC 1 (which controls the direct voltage) exceeds a certain value below the rated power, which, in the studied case was 0.8 pu.…”
Section: Eigenvalues Studymentioning
confidence: 99%
“…In [10], a procedure to derive the state space model for VSC-based multi-terminal HVDC systems (VSC-MTDC) was presented. The basis of the procedure was to implement state space models of the individual elements to be later interconnected as shown in Figure 1, where two converters are connected to the HVDC grid (a cable).…”
Section: Eigenvalues Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, VSC HVDC systems are characterised by faster control loops and system dynamics. This has triggered research efforts in small-signal modelling and analysis of VSC HVDC systems during the last decade [10][11][12][13][14][15]. The focus has largely been on model development for interaction studies with the surrounding ac grid, whilst incorporating the dynamics of the ac-and dc-sides of the HVDC converter station.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been common practice to undertake small-signal stability studies with the dc cables represented as either a single pi-equivalent circuit [10][11][12]15] or by multiple pi-equivalent circuits [13,14].…”
Section: Introductionmentioning
confidence: 99%